‘’An update on Brain organoids Generation and the Advancements made in the Context of a Human Model of Neurological Disorders-A systematic review’’ - Kaur, Kulvinder Kochar; Allahbadia, Gautam; Singh, Mandeep (British Journal of Healthcare and Medical Research, 2021)
Neurological conditions , represent a group of disorders that are responsible for the commonest etiologies of death all over the world which account practically for total cases of initiation of dementia in the aged ,besides their capacity ofhavinga negative impact on the motor capacity,mental and cognitive abilities andhaving a sense of total well being, besides happiness.At present maximum Neurological disorders(ND) remain without any appropriate treatment. In view of the absence of any effectivetherapeutic method.The cause for this is the existence of lack of insight with regards to the disorders,mainly due to thepresence of research models which do not possessthe capacity of translation into the human in vivo system.Thus here we conducted a systematic review utilizing search engine pubmed,google scholar ;web of science &others utilizing the MeSH terms like ND; NDG ;NDD; Alzheimer’s disease; Parkinson’s diseases; ASD ;TTH; viral infections; Induced pluripotent Stem Cells(iPSCs); Crisper/Cas genetic editing methods; 2D mono cell layer models ;3D organoid models; embryonic Stem Cells(ESCs);vascularization;neuroectodermal constituents;gas exchange;microglia role;mesodermal parts;cellular diversity; cellular interconnectivity;assembloids;cerebral organoids;evolutionary study;consciousness study; role in traumatic brain injury from 1980 till 2021 till date.We found a total of 1500 articles out of which we selected 102 articles for this review.No meta-analysis was done. The existent models for investigation of ND, Neurodevelopment(NDD) and drug crosstalk in the central nervous system(CNS), are inclusive of in vitro mono cell layer culture and in vivo animal models.There are limitations of these models with regards to translation of the research in the context of pathology of thedisorder, generation and treatment to humans. Brain organoids represent three dimensional(3D) cultures of Stem Cell obtained neural cells which simulate the generation of the in vivo humans brain,possessing high precision.Already the investigators have started the construction of these mini brains with the idea of modeling a wide variety of ND that are inclusive of the complicatedNDD, NDG.Here we have tried to detail the generation and theadvancements in this field.